Media Podsimak Memanfaatkan Google Podcast dalam Pembelajaran Menyimak Siswa Kelas VIII SMP Islam Darussalam - Ramadhani, Abd. Wafir; Alatas, Mochamad Arifin (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
Listening skills are one of the essential language competencies in learning Bahasa Indonesia. However, challenges still persist in delivering material that aligns with students' needs. Therefore, there is a need for innovative learning media to enhance listening skills. This study aims to describe the steps and stage of using Podsimak, an instructional innovation based on Google Podcast, as well as its impact on the listening skills of eighth-grade students at SMP Islam Darussalam. This research employed a descriptive qualitative approach, utilizing data collection techniques including participant observation and semi-structured interviews. The findings indicate that the learning process is carried out in three systematic stages: (1) pre-listening, (2) while-listening, and (3) post-listening. These stages are integrated into the use of the Podsimak application and show a positive effect on students' abilities to identify main ideas, extract detailed information, and summarize audio content. Thus, Podsimak can serve as an alternative digital learning medium that is contextual and aligned with 21st-century educational needs.